Thirty-day incidence of stroke after transcatheter aortic valve implantation: a meta- and network meta-analysis comparing self-expandable versus balloon-expandable valve prostheses. (25th November 2020) - Seppelt, P.C; Mas-Peiro, S; De Rosa, R; Murray, I; Fichtlscherer, S; Zeiher, A.M; Vasa-Nicotera, M
Abstract: Introduction: Stroke is a major and feared complication after transcatheter aortic valve implantation (TAVI). So far it is unknown, weather the valve deployment system itself has an impact on the incidence of periinterventional stroke. We sought to identify the incidence of 30-day stroke after transfemoral TAVI with self-expandable (SE) and balloon-expandable (BE) valves and performed a meta- and network meta-analysis to analyze differences related to the valve deployment system. Methods: Overall 2706 articles were searched comparing directly the performance of SE and BE TAVI valves, from which 7 were included for analysis (one randomized controlled trial, 6 propensity score matching studies) with a total number of 2488 patients. Meta-analysis used random effects model and reported risk ratios (RRs). To compare different type of valves a random-effects network meta-analysis based on a frequentist framework for indirect and mixed comparisons was applied and reported odds rations (ORs). Using P-Score the relative ranking probability of each valve was estimated and the hierarchy of competing valves was obtained. Results: Thirty-day incidence of stroke was 1.9% in SE (22 out of 1139, Medtronic CoreValve, Medtronic Evolut R and Pro, Boston Scientific ACURATE neo and St. Jude Medical Portico) and 3.1% in BE TAVI valves (42 out of 1349, Edwards Sapien 3 and XT) resulting in a RR of 0.65, (95% confidence interval (CI) 0.51 to 0.82). In accordance with the estimated P-Score CoreValve was the best effective for a reduction of 30-day stroke (72, 5%) whereas the worst were Sapien 3 and XT (19.%). Combined direct and indirect evidence showed no superiority of CoreValve compared with Sapien valves (OR 0.469, 95% CI 0.13–1.64) concerning 30-day stroke incidence. Conclusion: Our meta-analysis indicates a higher thirty-day incidence of stroke after TAVI with BE valves compared to SE valves. Furthermore, we could not find evidence for superiority of a specific valve system. Randomized controlled trials with head to head comparison of SE and BE valves are needed to address this open question. Funding Acknowledgement: Type of funding source: None